Paula Elkisch papers - Elkisch, Paula
Correspondence, notes, writings, and printed matter, chiefly 1947 to 1978, documenting Elkisch's work as a psychoanalyst. Includes case files used as subjects of her writings, articles on child psychiatry, and files relating to her study of German poet Rainer Maria Rilke.
Psychoanalyst.
Collection material in English, with German.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Sigmund Freud collection.
Keywords: Rilke, Rainer Maria, -- 1875-1926.; Child psychiatry; Psychoanalysis; Psychoanalysts